Structural Drivers of Risk-Taking in Indonesia’s Islamic Banks - Agus Suprapto; Mohammad Nur Rianto Al Arif; Indo Yama; Titi Dewi Warninda (Signifikan: Jurnal Ilmu Ekonomi, 2026)
Research Originality: This research is original in its focus on the long-run structural determinants of risk-taking in Indonesian Islamic banking. Research Objectives: The study aims to analyze how liquidity, profit-and-loss sharing (PLS), financing growth, financing-to-deposit ratio (FDR), economic growth, and inflation influence risk-taking behavior in Islamic banks. Research Methods: This study employs ARDL and Error Correction Model (ECM) techniques. The study investigates quarterly data from 2015 to 2024 to assess short-run and long-run relationships. The ECM framework provides insights into the adjustment mechanism toward equilibrium. Empirical Results: In the short run, liquidity, PLS, and financing growth significantly affect risk-taking. In the long run, liquidity has a significant negative effect, whereas PLS and Z-score exhibit a positive effect. Other variables are not statistically significant. The ECM confirms a strong adjustment mechanism, indicating that approximately 33.5% of short-run deviations are corrected toward long-run equilibrium each quarter. Implications: Policymakers and practitioners should design risk management strategies that differentiate between short-run operational adjustments and long-run macroeconomic anticipation. JEL Classification: C32, G21, G32, O16